Macroporous alumina- and titania-based catalyst for carbonyl sulfide hydrolysis at ambient temperature. (15th June 2019) - He, Enyun; Huang, Guan; Fan, Huiling; Yang, Chao; Wang, Hui; Tian, Zhen; Wang, Longjiang; Zhao, Yingrui
Graphical abstract: Highlights: Alumina/titania-based catalysts with 3DOM structure were synthesized successfully. The hydrolysis activity of the catalyst was enhanced remarkably by the 3DOM structure. The addition of P123 and SiO2 could further increase the hydrolysis activity. The most oxygenated hydrolysis product for the titania-based catalysts was sulfur. Abstract: In this study prepared alumina and titania carbonyl sulfide hydrolysis catalysts with three dimensional ordered macroporous (3DOM) structure were prepared by colloidal crystal template method. The fresh and used catalysts were characterized by X-ray diffraction, scanning electron microscopy, nitrogen adsorption studies, CO2 temperature programmed desorption (CO2 -TPD) and Fourier transform infrared spectroscopy. The hydrolysis performance of the catalysts and their resistances to oxygen poisoning were evaluated in a fixed bed reactor at room temperature. It was found that the hydrolysis activity of the catalysts was remarkably enhanced by introduction of 3DOM structure because the effective pulling out of the hydrolysis product H2 S from the porous structure significantly inhibited the deposition of sulfur on the surface of the catalysts. Adding surfactant P123 during the preparation of the 3DOM alumina-based catalyst increased the hydrolysis activity by increasing the surface area of the catalysts. Compositing SiO2 with the 3DOM titania-based catalysts could increase the surface area as well as benefit the formation of 3DOM structure. The optimum content of SiO2 was 33 wt%, at which both catalyst performance and the amount of basic sites as measured by CO2 -TPD were highest. The hydrolysis activity of the catalysts in the presence of oxygen showed that the oxygen toxicity resistance of the 3DOM titania-based catalysts were better than the 3DOM alumina-based catalysts. The most abundant sulfur specie deposited on the surface of the titania-based catalysts was elemental sulfur for the alumina-based catalysts it was sulfate species. Sulfate not only blocked the pores of the catalysts but also deactivated the catalysts seriously for its acidity.